Safety First, Safety Always: How Communication Drives Compliance through Culture in High-risk Mining Company - Johannes, Judith Caroline; Etikariena, Arum; Carissa, Bella (Yayasan Mata Pena Madani, 2025)
Safety in high-risk industries like mining remains a critical global concern. Despite the acknowledged importance of effective safety communication, the mechanisms through which it fosters long-term compliance and integrates with organizational safety culture are underexplored, particularly in Indonesia. This study aims to fill this gap by examining how safety communication influences compliance and highlighting the role of organizational safety culture in mediating compliance. Using a quantitative approach, data were gathered from 204 employees of an Indonesian high-risk mining company (PT X) through a digital survey conducted in October 2024. The Hayes Process Model 4, with a bootstrapping approach of 5000 samples, was employed to evaluate relationships between safety communication, safety culture, and compliance. Findings indicate that safety communication directly affects compliance and indirectly affects safety culture. This partial mediation underscores the safety culture's essential role in enhancing effective communication. By focusing on Indonesia’s mining sector, this study uniquely addresses the contextual challenges of a high-risk industry and offers insights applicable to similar sectors globally. The findings bridge a critical gap in understanding the interplay between communication and cultural factors in safety compliance. Organizations can leverage these findings to design targeted communication strategies and cultural reinforcement initiatives, ensuring sustained compliance and safer working environments.